GRIYA YATIM PUTERI BANJARBARU - Ihsanul Hakim; Muhammad Deddy Huzairin (JURNAL TUGAS AKHIR MAHASISWA LANTING, 2021)
Griya Yatim Puteri banjarbaru is a dormitory branch of Griya Yatim and Dhuafa Mentaos Banjarbaru as a home for orphaned girls with all their activities with foster parents and located in Banjarbaru City. With the architectural problem, how is the design of Griya Yatim Putri Banjarbaru which is to become a child-friendly residence". By using the Behavioral Architecture method and applying the principles of Child Friendly Architecture and the Concept of Flexibility Architecture to solve problems. In the end, the design of Griya Yatim Putri Banjarbaru could be realized as a single-phase building with a capacity of 20 assisted children, having sufficient space facilities to meet the needs of residents, especially the assisted children in developing themselves..